2013
DOI: 10.1186/1471-2458-13-627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of risk factors, activities and psychological disorders on the health of patients with chronic obstructive pulmonary disease in China: a cross-sectional study

Abstract: BackgroundPatients with chronic obstructive pulmonary disease (COPD) often have organ dysfunction and resulting poor quality of life; however, in China little information is available regarding factors that affect their health. Here, the relationship between risk factors, activities and psychological disorders and health of patients with COPD in rural areas of Xuzhou, China was assessed.MethodsA cross-sectional study of 7597 COPD patients randomly selected by place of residence from 24,641 COPD patients who ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Previous reviews indicated that up to 55% of patients with COPD may have a clinical anxiety disorder 8,9. One cross-sectional study in China showed the prevalence of anxiety at approximately up to 57.1% 10. Despite the high prevalence of anxiety in patients with COPD, it is often neglected and undermanaged 11.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews indicated that up to 55% of patients with COPD may have a clinical anxiety disorder 8,9. One cross-sectional study in China showed the prevalence of anxiety at approximately up to 57.1% 10. Despite the high prevalence of anxiety in patients with COPD, it is often neglected and undermanaged 11.…”
Section: Introductionmentioning
confidence: 99%
“…In Lou et al's study [30] of 1100 COPD patients conducted in Xuzhou, the prevalence rate of depression in COPD patients was 18.3 % as measured by the Hospital Anxiety and Depression Scale (HADS). In rural China, Zhang et al's study [31] showed that 28.3 % of COPD patients had depressive symptoms as screened by the study questionnaire. Similar prevalence rate of depressive symptoms (22.8 %) was observed in Chinese COPD patients in a Singaporean study [32] that used GDS as a screening tool.…”
Section: Prevalence Of Depression In Copd Patientsmentioning
confidence: 98%
“…In the above studies [21,[29][30][31][32][33], the mean age of COPD subjects ranged from 59 to 65 years. In contrast, majority of COPD patients in our study were from geriatric population (mean age 75 years).…”
Section: Prevalence Of Depression In Copd Patientsmentioning
confidence: 99%
“…In developing countries such as China, the high incidence of COPD is a major public health concern (Zhou and Chen, 2013;Zhang et al, 2013). COPD is correlated with various factors, including infection, genetics, and environmental exposure (particularly cigarette smoke).…”
Section: Introductionmentioning
confidence: 99%